2020
DOI: 10.1111/jnc.15225
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia risk candidate EGR3 is a novel transcriptional regulator of RELN and regulates neurite outgrowth via the Reelin signal pathway in vitro

Abstract: Schizophrenia is a severe psychiatric disorder with a strong hereditary component that affects approximately 1% of the world's population. The disease is most likely caused by the altered expression of a number of genes that function at the level of biological pathways or gene networks. Transcription factors (TF) are indispensable regulators of gene expression. EGR3 is a TF associated with schizophrenia. In the current study, DNA microarray and ingenuity pathway analyses (IPA) demonstrated that EGR3 regulates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“… 52 For example, EGR3 regulates neuronal growth through the Reelin signaling pathway. 53 Additionally, it is highly expressed in various tumors and is involved in tumor progression. 54 Studies have shown that EGR3 regulates estrogen‐mediated invasion of breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 52 For example, EGR3 regulates neuronal growth through the Reelin signaling pathway. 53 Additionally, it is highly expressed in various tumors and is involved in tumor progression. 54 Studies have shown that EGR3 regulates estrogen‐mediated invasion of breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…EGR3 is found to be involved in neurodevelopmental processes 52 . For example, EGR3 regulates neuronal growth through the Reelin signaling pathway 53 . Additionally, it is highly expressed in various tumors and is involved in tumor progression 54 .…”
Section: Discussionmentioning
confidence: 99%
“…Further analysis demonstrated that 5fC was localized in genomic regions with higher chromatin accessibility and increased levels of binding of RNA pol II, indicating a potential role for 5fC in promoting gene transcription in neurons. Motif analysis also identified several potential reader proteins for 5fC, including members of the forkhead box (FOX) family and the zinc finger (ZNF) family, which have been previously identified as 5fC readers in proteomic screening studies. , We have experimentally demonstrated that EGR3 is a 5fC-binding protein that has been reported to possess DNA-binding transcriptional activation activity and sequence-specific DNA-binding activity, and be involved in the positive regulation of transcription by RNA polymerase II. , Overall, accumulating evidence suggests that 5fC not only acts as an intermediate in active DNA demethylation but also participates in functional gene regulation. Further studies are warranted to fully understand the precise mechanisms underlying the regulatory function of 5fC in neurons.…”
Section: Discussionmentioning
confidence: 99%
“…18,20 We have experimentally demonstrated that EGR3 is a 5fC-binding protein that has been reported to possess DNA-binding transcriptional activation activity and sequence-specific DNA-binding activity, and be involved in the positive regulation of transcription by RNA polymerase II. 50,51 Overall, accumulating evidence suggests that 5fC not only acts as an intermediate in active DNA demethylation but also participates in functional gene regulation. Further studies are warranted to fully understand the precise mechanisms underlying the regulatory function of 5fC in neurons.…”
Section: ■ Discussionmentioning
confidence: 99%
“…From molecular mechanisms in cultured cells (Agbaegbu Iweka et al, 2021; Bendahmane et al, 2020), neurochemical mechanisms in intact organisms (Abreu et al, 2021; Becker et al, 2021), new imaging and quantitative methodologies providing insight into neurochemical changes (Abdalla et al, 2020; Arber et al, 2021; Blank & Hopf, 2021; Dienel, 2021) and critical biomarkers in disease (Altmayer et al, 2021; Chakraborty & Basu, 2021; Chatterjee et al, 2021; Eden et al, 2021; Geula et al, 2021; Ginsberg et al, 2021; Glezer et al, 2021), the scope of the Journal of Neurochemistry has broadened to respond to the demands of our scientific community. Neurochemical mechanisms of disease are a popular topic covering neuropsychiatric and developmental disorders (Haase et al, 2021; Kozlowska et al, 2021; Liu & McNally, 2021; Nie et al, 2021; Nomura et al, 2021) and neurodegenerative diseases (Brosseron et al, 2021; Butler et al, 2021; Chatterjee et al, 2021; Korecka & Shaw, 2021; Sathe et al, 2021; Trinh et al, 2021; Yuede et al, 2021). Similarly, studies into neuroinflammation and neuroimmunology are a growing area within the journal, such that in 2021 we published a special issue dedicated to this topic (https://onlinelibrary.wiley.com/toc/14714159/2021/158/1).…”
Section: Figurementioning
confidence: 99%